(untitled) (Baghdad Science Journal, 2019)
The thermodynamic constanting of “crude and partially purified” Paraxonase(PON) was evaluated in the sera of “healthy and ectopic” pregnant women in order to characterize the reaction of PON with diethyl para-nitro phenyl phosphate as substrate.This study was performed on (17) women with ectopic pregnancy (EP) whose age between (25-55) years and (25) normal pregnant women with a mean age of (25 -55) years as a control group . Samples were collected from the Medical City, AL-Yarmook and Fatema AL-Zahraa hospitals during the period from Sep.2011 to April 2012.The study included the evaluation of “paraxonase activity, specific activity and total protein” in the (crude and partially purified) sera of EP patients & healthy subjects. The results demonstrated that there was significant decline (p≤0.05) in the activity and specific activity of PON and significant increase (p≤0.05) in the protein concentration. The study also included the evaluation of the energetic parameters: the Gibb`s free energy (ΔG) enthalpy change (ΔH), heat of activation,(ΔH*), entropy change(ΔS), temperature coefficient (Q10) and activation energy (Ea) with respect to human PON. The results indicated that there was a dramatic increase in each of the thermodynamic parameters (ΔG,Ea,ΔH,ΔS,ΔH*,Pz,Q10) for purified PON compared with enzyme in crude sera. The results indicated also that there was a dramatic increase in each of the thermodynamic parameters (ΔG, Ea, ΔH,ΔS,ΔH*,Pz,Q10) for purified PON compared with enzyme in crude sera which indicated that the purified PON suffered from the lack metals or substances that help enzyme to over come energy barrier, at the same time the purified PON(the freedom enzyme) had the greatest chance to collide and create of the favorable orientation with substrate.